The Influence of Using Learning Media on Students' Interest in Learning in Class VIII SMP Muhammadiyah 57 Medan - Ahmad Danu Annaafi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The aim of this study is to analyze the impact of using learning media on students' interest in learning in class VIII at SMP Muhammadiyah 57 Medan. The method applied is quantitative with a quasi-experimental design. The research sample consists of 60 students divided into two groups: one group uses interactive learning media, while the other follows conventional learning methods. Data were collected through questionnaires and observational analysis. The results indicate that the group using interactive media showed a significant increase in interest in learning, with an average score of 78.5 compared to 65.4 in the conventional group. These findings suggest that the application of varied learning media can enhance student motivation and engagement in the learning process, and recommend the use of more innovative media in the curriculum.